The post-orchiectomy systemic inflammatory index is associated with tumor characteristics in clinical stage I germ cell tumors - Lesko, Peter; Mego, Michal (Frontiers in Oncology, 2025)
BackgroundApproximately 25% to 30% of clinical stage I (CSI) germ cell cancer (GCT) patients will experience disease relapse after an orchiectomy. Adding adjuvant treatment will decrease the relapse rate but could lead to over-treatment. Prognostic biomarkers such as lymphovascular invasion (LVI) and/or embryonal carcinoma (EC) in non-seminoma (NSGCT) and rete testis invasion (RTI) and/or primary tumor size (PTS) in seminoma (SGCT) add limited value in treatment decision- making. The aim of this study is to assess the systemic inflammatory index (SII) and lactate-dehydrogenase (LDH) with clinicopathological findings along with their prognostic impact.MethodsThis is a retrospective study that included 159 diagnosed CSI GCT patients, who underwent active surveillance (AS) from June 2004 to November 2023. Medical records and pathology reports were collected retrospectively. Drawn blood must have been done less than 3 months after the orchiectomy had been done. For the survival analysis, we used dichotomized values of the studied biomarkers from “low” to “high” based on the median values.ResultsThe median follow-up time was 61 months (ranging from 1 to 230 months), with 2-year relapse- free survival (RFS) of 81.3% and 69.0% in SGCT and NSGCT, respectively. We confirm inferior RFS in the presence of LVI compared to an absence of LVI in NSGCT ([HR]= 2.59, 95%CI (0.74-9.07), p=0.04). A trend of inferior RFS in NSGCT patients with EC predominance (≥50%) was also observed ([HR]= 2.59, 95%CI (0.98-6.85), p=0.06). A prognostic impact of RTI and a PTS >4cm in SGCT was not observed with p=0.24 and p=0.51, respectively. The SII was assessed in the population, and a higher neutrophil- to- lymphocyte ratio (NLR) value was associated with LVI presence and with advanced tumor stage in NSGCT. In SGCT, a higher SII level was associated with LVI presence and advanced pathological stage. A PTS >4cm was associated with a higher LDH level among all the studied patients, without significance in SGCT or NSGCT. A higher LDH value in NSGCT was also associated with EC predominance (≥50%).ConclusionOur study, for the first time, revealed associations of post-orchiectomy systemic inflammatory indices and/or LDH in CSI GCT. These new associations deserve further evaluation in a larger cohort of patients with CSI GCT to elucidate whether its associations in certain histology subgroups will improve the stratification of the at-risk population.